Synoptic Circulation Impact on the Near‐Surface Temperature Difference Outweighs That of the Seasonal Signal in the Eastern Mediterranean. Issue 20 (17th October 2018) - Lensky, Itamar M.; Dayan, Uri; Helman, David
Abstract: Near‐surface temperature difference (i.e., the difference between land surface skin and 2‐m air temperatures—Δ T ) drives numerous ecological and biophysical processes on Earth, constituting an essential parameter in process‐based Earth System Modeling. Δ T is known to be governed by factors like incoming solar radiation and wind, which vary according to synoptic‐scale circulation via horizontal pressure gradient and cloud cover. Δ T is also affected by land surface characteristics and vegetation dynamics. Here we assess the role of seasonality, synoptic‐scale circulation, and vegetation dynamics, using satellite normalized difference vegetation index (NDVI) and latent heat estimates, on the Δ T in the Eastern Mediterranean (EM). Δ T was calculated using land surface temperatures derived from the Moderate Resolution Imaging Spectroradiometer and air temperatures measured at 94 meteorological stations in the EM for 2006–2010. The effect of circulation on Δ T is demonstrated for four synoptic categories covering all seasons, showing that the influence of synoptic‐scale circulation may be sometimes stronger than that of the seasonal signal in this region. Δ T showed negative relationships with NDVI indicating that vegetation is attenuating the near ground temperature difference, with a gradual effect increasing from southern drylands to the more humid northern vegetated areas in the EM. The relationship between Δ T and NDVI was stronger for specific synoptic classes than for seasonal division, implying the combined role of vegetation cover dynamics and synoptic‐scale conditions on Δ T . Findings from this study show promise for continuous spatiotemporal estimations of Δ T from land surface temperature and NDVI satellite data. Key Points: We assess the role of seasonality, synoptic‐scale circulation, and vegetation (NDVI and LE) on the near‐surface temperature difference Relationship between the near‐surface temperature difference and NDVI was stronger for specific synoptic classes than for seasonal division Synoptic circulation impact on the near‐surface temperature difference outweighs that of the seasonal signal for some synoptic classes